Complete Sequence of pEC012, a Multidrug-Resistant IncI1 ST71 Plasmid Carrying blaCTX-M-65, rmtB, fosA3, floR, and oqxAB in an Avian Escherichia coli ST117 Strain - Pan, Yu-Shan; Zong, Zhi-Yong; Yuan, Li; Du, Xiang-Dang; Huang, Hui; Zhong, Xing-Hao; Hu, Gong-Zheng (Frontiers in Microbiology, 2016)
A 139,622-bp IncI1 ST71 conjugative plasmid pEC012 from an avian Escherichia coli D-ST117 strain was sequenced, which carried five IS26-bracketed resistance modules: IS26-fosA3-orf1-orf2-∆orf3-IS26, IS26-fip-∆ISEcp1-blaCTX-M-65-IS903D-iroN-IS26, IS26-∆tnpR-blaTEM-1-rmtB-IS26, IS26-oqxAB-IS26 and IS26-floR-aac(3)-IV-IS26. The backbone of pEC012 was similar to that of several other IncI1 ST71 plasmids: pV408, pM105 and pC271, but these plasmids had different arrangements of multidrug resistance region. In addition, the novel ISEc57 element was identified, which is in the IS21 family. The stepwise emergence of multi-resistance regions demonstrated the accumulation of different resistance determinants through homologous recombination. To the best of our knowledge, this is the first study to identify a multidrug-resistant IncI1 ST71 plasmid carrying blaCTX-M-65, rmtB, fosA3, floR and oqxAB in an avian E. coli ST117 strain.